Analisis Dampak Perubahan Tataguna Lahan Sub DAS Beringin di Bukit Semarang Baru Terhadap Peningkatan Debit Sungai Beringin Kota Semarang - Sumiyadi (Jurnal Teknik Sipil dan Perencanaan)
The changes of landuse in watershed area of Beringin river, from rubber forest into housing area of Bukit Semarang Baru (BSB), is suspected as the cause of increase in water discharge into Beringin river. The research objective is to describe the rise in water discharge of Beringin river due to the changes of landuse in the watershed area of Beringin river which currently inhibited by BSB housing. According to statistics criteria, the distribution of maximum daily rainfall frequency for repeated period of 2, 5, 10 and 20 years was analyzed by distribution frequency Gumbel. Research result shows that there is an increase in water discharge of Beringin river due to the rise of runoff water as the consequence of land use change in BSB area. Ten years discharge before the land use change was = 7,94 m /dt, then raised into 113,49 m3 /dt following the change, so the water discharge of Beringin river is = 121,43 m3 /dt. This impact analysis can be an early information for the future researcher to find the solution of flood phenomena in Semarang.